Socio-economic and Demographic Determinants of Household Fertility Decisions - Endurance Uzobo (Clinical Sociology Review)
This study investigates the socio-economic and demographic determinants of household fertility decisions in Nigeria. Using the family system model as framework, a cross-sectional survey design in a retrospective study was adopted. Quantitative data were purposively gotten from the 2018 Nigeria Demographic and Health Survey (NDHS) household recode dataset.  Data were analysed using descriptive statistics and Logistic Regressions at P<0.05. The mean age at first birth of respondents was 18.8±4.0 years. The mean of Children ever-born was 5.9±2.8. The Children ever-born was highest in the North West region (36.7%), while the South East had the least (12.6%) sum of Children ever-born in the six regions. The relationship between children ever-born and the age at first birth is statistically significant (χ2= 8334.4, p=<0.001). Women with all living are 2.0 times (OR=2.071, CI=1.987-2.158) more likely to increase their Children ever-born than women who have experienced the loss of a child. Women who have no formal education are 5.8 times (OR=5.835, CI=5.504-6.186) more likely to increase their Children ever-born than women with tertiary education. Women who do not utilize contraception in any way and those who used the folkloric method were respectively 0.8 times and 5.5 times more likely to increase their children ever-born than women using modern contraceptives respectively. Based on the findings, it is recommended that fertility controls must be prioritized, specifically by encouraging girl child education across the nation.